Evaluation of Antitumer activity of Ammi Majus seeds extract on Some cancer cell line - Shahd Amer Ismael; Izdehar Mohammed Jasim; Saba Adnan Abbas (Academic Science Journal)
Cancer is one of the major health problems in the world and is one of the important causes of an increase in deaths among children and adults , Today many of the treatment methods are used to treat cancer. Unfortunately, in most cases very poor response is often associated with undesirable side effects has been made researchers to achieve more effective drugs with fewer side effects. The current study aimed to detect the effect of Ammi majus seeds extracts ( aqueous and ethanolic extracts) in treating somecancerous lines (HepG2 and Hela )  human cancer cell lines.The current study was perfomedin Iraqi Center for Cancer and Medical Genetics Research (ICCMGR) in Baghdad from December to March (2023). The cancer cell lines were treated with different concentrations (6.25 ,12.5 ,25, 50, 100,200 )of the Ammi majus seeds extracts  (aqueous and ethanolic extracts).The results showed the effect of both seeds extracts (aqueous and alcoholic) on the growth of Helacell lines increased with increasing the concentration and give highest inhibition rate( 3.93 ± 72.69 % and 3.93±   91.87 ) in respectively ,at a concentration  ( 200 µg/ml,)Wheareas the highest inhibition rate for the seedsextracts (aqueous and alcoholic) on the growth of HepG2 was ( 3.18 ± 68.86 % and 1.36±   79.31 %) in respectively, at a concentration ( 200µg/ml ), ​The current study concluded that the aqueous and alcoholic extracts of the Ammimajus seeds plant has an effect in the process of inhibiting cancer cell lines.making this plant a promising candidate for cancer treatment.